2016
DOI: 10.1101/071746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Influence of a mono-frequency sound on bacteria can be a function of the sound-level

Abstract: Chromobacterium violaceum was subjected to sonic stimulation with 300 Hz sound, at five different levels of loudness in the range of 70 -89.5 dB. Sonic stimulation was found to affect bacterial growth and quorum sensing regulated pigment (violacein) production significantly. Magnitude of this effect was found to be dependent on sound-level. The minimum critical difference required to cause any statistically significant change in bacterial response with respect to sound-level was found to be 13 dB. Growth of C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Liu et al (2016) indicated the possibility of increased release of chemical mediators of QS in sound-exposed endospores. We have also shown altered production of QS-regulated pigments in sound-exposed bacterial cultures Kothari et al, 2018). QS being an important regulator of virulence (Natrah et al ., 2011), any chemical or physical agents capable of modulating QS can be expected to modulate bacterial virulence too.…”
Section: Effect Of Sonic Stimulation On Bacterial Virulencesupporting
confidence: 63%
See 1 more Smart Citation
“…Liu et al (2016) indicated the possibility of increased release of chemical mediators of QS in sound-exposed endospores. We have also shown altered production of QS-regulated pigments in sound-exposed bacterial cultures Kothari et al, 2018). QS being an important regulator of virulence (Natrah et al ., 2011), any chemical or physical agents capable of modulating QS can be expected to modulate bacterial virulence too.…”
Section: Effect Of Sonic Stimulation On Bacterial Virulencesupporting
confidence: 63%
“…Previously we have reported results of our in vitro experiments describing (a) effect of low power MW on microbial growth/metabolism , protein synthesis , enzyme activity (Dholiya et al, 2012), exopolysaccharide production , toxin production (Ramanuj et al, 2015), quorum-sensing (QS) regulated pigment production (Chaudhari et al, 2014), etc. ; effect of sonic stimulation on microbial growth (Sarvaiya and Kothari, 2015;Shah et al, 2016), antibiotic susceptibility (Sarvaiya and Kothari, 2017), and QS-regulated pigment production Kothari et al, 2018). Mutagenic effect of MW has also been previously described by us (Gosai et al, 2013;Kothari et al, 2014).…”
Section: Introductionmentioning
confidence: 53%
“…Considering that IMT had no significant effect regarding biomass concentration, this data suggests that intermittence influences the enhancement of protein production yield in each cell and not because of biomass increment. Although most studies addressing the effect of sound over biomass have used continuous signals, in the present research work, the establishment of the effect of intermittence was considered important. Intermittence parameters were either selected as continuous signal or an intermittent cycle of 20 min sound plus 20 min silence; this value was assigned in relation to E. coli duplication time under typical growth conditions …”
Section: Resultsmentioning
confidence: 99%
“…7 Furthermore, it has been reported that sound can also upregulate the activity of kinases, disulfide oxidases, chaperones, signal transporters, and genes involved in RNA production in bacteria. 26 Considering that their treatments used sound beeps instead of continuous signals, it is likely that those reported effects are due to intermittence.…”
Section: Effect Of Individual Sound Elements Over Biomass Concentratimentioning
confidence: 99%
See 1 more Smart Citation